Comparison of the capacity of different jump and sprint field tests to detect neuromuscular fatigue - Gathercole, R. J.; Sporer, B. C.; Stellingwerff, T.; Sleivert, G. G. (The Journal of Strength and Conditioning Research, 2015)
Different jump and sprint tests have been used to assess neuromuscular fatigue, but the test with optimal validity remains to be established. The current investigation examined the suitability of vertical jump (countermovement jump [CMJ], squat jump [SJ], drop jump [DJ]) and 20-m sprint (SPRINT) testing for neuromuscular fatigue detection. On 6 separate occasions, 11 male team-sport athletes performed 6 CMJ, SJ, DJ, and 3 SPRINT trials. Repeatability was determined on the first 3 visits, with subsequent 3 visits (0-, 24-, and 72-hour postexercise) following a fatiguing Yo-Yo running protocol. SPRINT performance was most repeatable (mean coefficient of variation =2%), whereas DJ testing (4.8%) was significantly less repeatable than CMJ (3.0%) and SJ (3.5%). Each test displayed large decreases at 0-hour (33 of 49 total variables; mean effect size = 1.82), with fewer and smaller decreases at 24-hour postexercise (13 variables; 0.75), and 72-hour postexercise (19 variables; 0.78). SPRINT displayed the largest decreases at 0-hour (3.65) but was subsequently unchanged, whereas SJ performance recovered by 72-hour postexercise. In contrast, CMJ and DJ performance displayed moderate (12 variables; 1.18) and small (6 variables; 0.53) reductions at 72-hour postexercise, respectively. Consequently, the high repeatability and immediate and prolonged fatigue-induced changes indicated CMJ testing as most suitable for neuromuscular fatigue monitoring.